IMPLEMENTASI BUDAYA RISET SEBAGAI MEDIA PENGEMBANGAN POTENSI PUSTAKAWAN PADA TAMAN BACAAN MASYARAKAT WADAS KELIR PURWOKERTO - Mukhamad Hamid Samiaji; Khomsiyatun, Umi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
Community Reading Gardens (TBM) is a form of lifelong learning facility that is expected to be able to increase people's interest in reading and literacy. More broadly, TBM provides access to information and educational resources that can stimulate the public to conduct research. The purpose of this study is to analyze the implementation of research culture as an effort to develop the potential of librarians in the Wadas Kelir Purwokerto Community Reading Park. The results of this study are: 1) the research culture for librarians was formed with the hope that librarians can follow the TBM curriculum development activities through the publication of scientific papers, the hope that librarians can live independently, and the hope that librarians can maintain the tradition of reading and writing; 2) the implementation of research culture is prioritized for the internal librarians of TBM Wadas Kelir and the general public by organizing various journal writing trainings, reference management training, and writing practices "one week one research"; 3) The research learning method of TBM librarians is carried out by lectures, dialogues, and the task of making research articles, while the strategies applied are to increase motivation, introduction to theory, and good practice in writing research articles and publishing scientific papers; 4) Results and Benefits of Research Culture for librarians, namely an increase in both their human resources (achievement, high number of scientific publications) and material resources (reward/honorarium for loading scientific papers); and 5) the research culture as a semi-autonomous TBM curriculum is basically an innovative activity that reflects the purpose of the establishment of TBM. Therefore, this support cannot be separated from other learning included in the official TBM curriculum. As part of the research competency process, TBM offers librarians the opportunity to work as a Rosette team in the form of a service. These facilitation activities by TBM are called "short-term goals" and aim to achieve results that are used to meet financial needs.